1999
DOI: 10.1111/j.1469-445x.1999.01868.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Altered Body CO2 Stores on Pulmonary Gas Exchange Dynamics During Incremental Exercise in Humans

Abstract: summaryThe lactate threshold is a widely used and, at times, controversial construct in exercise physiology and pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 27 publications
1
24
1
1
Order By: Relevance
“…One subject was removed from data analyses due to large breath-to-breath variability in breathing pattern data recorded during incremental exercise. Another four participants were excluded from analyses due to a high-risk of pseudo-G EX 1 detection-marked by an abnormally high ([1.0) respiratory exchange ratio during the initial stages of the incremental protocol (Cannon et al 2009;Ozcelik et al 1999;Whipp 2007). The € f R 1 and € f R 2 were successfully identified in all remaining subjects (n = 23) using the polynomial spline smoothing technique.…”
Section: Resultsmentioning
confidence: 99%
“…One subject was removed from data analyses due to large breath-to-breath variability in breathing pattern data recorded during incremental exercise. Another four participants were excluded from analyses due to a high-risk of pseudo-G EX 1 detection-marked by an abnormally high ([1.0) respiratory exchange ratio during the initial stages of the incremental protocol (Cannon et al 2009;Ozcelik et al 1999;Whipp 2007). The € f R 1 and € f R 2 were successfully identified in all remaining subjects (n = 23) using the polynomial spline smoothing technique.…”
Section: Resultsmentioning
confidence: 99%
“…The ventilatory threshold was identified as the first breakpoint in the _ V CO 2 versus _ V O 2 relationship (Beaver et al 1986). The criteria proposed by Ozcelik et al (1999) as indicative that a genuine rather than a pseudo threshold has been identified were met in all subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Ventilation and pulmonary gas exchange were measured breath-by-breath using an Oxycon a system (Jaeger, Hochberg, Germany). The lactic acidosis threshold (h L ) was estimated using the V-Slope (Beaver et al 1986) method and related indices (Ozcelik et al 1999). Patients performed the constant WR exercise tests in a randomized sequence (on different days) at an intensity of 80% of that of h L , and at two levels above the pretraining work-rate at the lactic acidosis threshold (WRh L ).…”
Section: Methodsmentioning
confidence: 99%